2011
DOI: 10.1038/leu.2011.271
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leukemia activity of chaetocin via death receptor-dependent apoptosis and dual modulation of the histone methyl-transferase SUV39H1

Abstract: Epigenetic deregulation is involved in acute myeloid leukemia (AML) pathogenesis and epigenetic targeting drugs are in clinical trial. Since the first results with histone-deacetylase inhibitors in AML are controversial, novel single and combined treatments need to be explored. It is tempting to combine chromatin-targeting drugs. SUV39H1, the main methyl-transferase for lysine 9 tri-methylation on histone H3, interacts with oncogenes involved in AML and acts as a transcriptional repressor for hematopoietic dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 51 publications
4
56
0
1
Order By: Relevance
“…6 As gliomas are refractory to current treatment strategies, we investigated whether Chaetocin could affect glioma cell proliferation. Treatment with Chaetocin induced glioma cell death in a dose- (Figure 1a) and time- (Figure 1b) dependent manner.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 As gliomas are refractory to current treatment strategies, we investigated whether Chaetocin could affect glioma cell proliferation. Treatment with Chaetocin induced glioma cell death in a dose- (Figure 1a) and time- (Figure 1b) dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…6 As we have reported that elevated ROS level induces glioma cell apoptosis, 2 we determined ROS levels in Chaetocin-treated cells with reduced thioredoxin reductase activity. A significant 4–6-fold increase in ROS production was observed in A172, T98G and U87MG glioma cells upon Chaetocin treatment indicated by increased DCFDA and DHE fluorescence intensity (Figure 1d).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the treatment of human hepatoma cells with curcumin (Cur) (dietary pigment derived from Curcuma longa) led to a significant ROS-dependent HAT-catalyzed decrease in histone acetylation [25]. The HAT inhibitor chaetocin suppressed methyltransferase SUV39H1through lysine 9 trimethylation on histone H3 and induced apoptosis in leukemia cells by a ROS-dependent mechanism [26]. All these conflicting data are presented in Figure 3.…”
Section: Ros/rns Signaling In Dna Methylationmentioning
confidence: 94%
“…Chaetocin ROS SUV39H1 (HAT) histone H3Me 3 trimethlation Leukemia cell apoptosis [26] Overexpression of Sirt1 suppressed ROS formation produced by the adaptor protein p66Shc and inhibited high glucose-induced p66Shc upregulation in human umbilical vein endothelial cells. It was suggested that Sirt1suppressed the acetylation of histone H3 bound to p66Shc promoter region [33].…”
Section: Ros Signaling In the Class III Histone Deacetylasesmentioning
confidence: 99%